Cold regions engineering 2012 : sustainable infrastructure development in a changing cold environment : proceedings of the 15th International Specialty Conference on Cold Regions Engineering : August 19-22, 2012, Quebec City, Canada - Doré, Guy; Morse, Brian (American Society of Civil Engineers, 2012)
Proceedings of the 15th International Specialty Conference on Cold Regions Engineering, held in Quebec City, Canada, August 19-22, 2012. This collection contains 82 peer-reviewed papers on new developments in cold regions engineering and technologies. These papers offer a truly international view of the current state of knowledge in different aspects of civil engineering in cold regions, including geotechnics, transportation, pavements, structures, rivers and ports, and water management. Topics include: embankment engineering on permafrost; foundation design; frozen soil behavior; infrastructure and climate change; mining in cold regions; navigation in seasonal frozen waterways; permafrost investigation; port engineering; river ice processes; roads: pavement design, spring load restrictions, and winter road maintenance; snow and ice; structural engineering; and wastewater management in a cold climate. This collection will be of interest to all types of civil engineers working in areas where cold weather is a factor in engineering practice. --